Perbandingan Kadar Kafein pada Jenis Kopi Hasil Perkebunan Bengkulu dengan Metode Spektrofotometri Ultraviolet - elly mulyani; Herlina Herlina; Dewi Winni Fauziah; Aina Fatkhil Haque (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
Bengkulu is a province that is in the top five as a coffee producer in the archipelago. The survey proves that Bengkulu has a fairly large potential for producing coffee with many local coffee products from Bengkulu city plantations that are already circulating in the market. Caffeine is a type of alkaloid found in coffee beans, tea leaves, and cocoa beans. This study aims to determine the caffeine content of Bengkulu plantations (Rejang Lebong, Kepahiang, Seluma) using Ultraviolet Spectrophotometry. The results showed that the coffee samples at the Bengkulu Plantation contained caffeine with levels, namely: 0,00144 mg (Seluma coffee sample), 0,011928 mg (Rejang Lebong coffee sample), 0,019,144 mg (Kepahiang coffee sample). Of the three data, the highest plantation caffeine content was found in Kepahiang coffee.